Women’s knowledge about risk factors and early detection methods of breast cancer: A case study of the Library Network, University of Colombo - Manatunga, P.K.S. (The Library, University of Colombo, 2019)
Breast cancer has been identified as the most prominent cancer type which affects women worldwide and there is a gradual increase of breast cancer incidences yearly in Sri Lanka. Late diagnosis of breast cancer at advanced stages results in less or no benefit from any form of treatment. Identifying breast cancer risk factors and early detection methods could be recognized as two major variables, which affect early diagnosis and screening. The objective of this study is to find the extent of knowledge held by the female employees of the Library Network of the University of Colombo on the above two variables. Data were obtained from 40 women, which is the total population, using a self-completion, closed ended questionnaire and descriptive analysis was done. The most frequently identified risk factor was early age at menarche (75%). The present study revealed that women, who are employed in the Library Network, have inadequate knowledge about several risk factors, including late age at menopause, high alcohol consumption and high animal fat intake and also a false belief that giving birth to more than 5 children and first gestation before the age of 25 as non-risk factors. Healthy diet was identified by the majority (80%) as a possible preventive measure. Mammography and self–breast examination as methods for early detection was identified by 77.5% and 82.5% of the participants respectively. Of the 40 participants, 4 and 29 are likely to have a good (≥ 75%) and average knowledge (75%-50%), about risk factors and their prevention respectively, while others have a fair (50%-25%) knowledge. Average knowledge of the academic staff on the same factors is 65.15%, while that of the non-academic staff is 54.80%. The most often cited sources of information about risk factors and early detection methods were newspapers (75%) and the medical officer (7.14%) was the least cited source. The study recommends the need for enhanced educational programmes to improve knowledge about breast cancer risk factors and early detection methods. The findings of this study and further studies could be used for successful knowledge generation among females in Sri Lanka. Future studies should focus on knowledge about breast cancer and the influence of socio-economic variables in order to develop an institutional framework and policy guideline to enhance adequate and urgent dissemination of information about breast cancer among all women in the system.
Keywords: breast cancer, information needs, information sources